educational research and evaluation capacities development - Nuñez Flores, María Isabel (2012)
The study analyzes the relationship of research and evaluation and its effect on the development of research capacities in students of the Research Workshop II, corresponding to the 8 cycle of the school academic professional education at the Faculty of Education and students Seminar IV research, the 8 th th cycle of School Sociology, Faculty of Social Sciences of San Marcos University. Focuses research as an end and a weighted function and relevant higher education. Contradictory less formal production practice and therefore has insufficient resources and requires a theoretical and methodological practice, rigorous and constant work with reality as it is changed by the development of science and technology in the production knowledge, supplied tools and operating mode. Assume evaluation as process and product of the educational action. Continuous, systematic, objective inherent to the teaching – learning process. Thus represents an axis in the evaluation, estimation, measurement and interpretation of the objectives achieved and targets. It addresses a major problem en scope in developing the skills, necessary because the current labor market demands competitive and innovative. And being a complex research requires an assessment which becomes efficient and effective measurement feedback, converged on learning and self learning. But regardless of the values.